More on the Energy/Non-Energy Commodity Price Link - Baffes, John (2012)
This paper examines the energy/non-energy commodity price link, based on a reduced form econometric model and using annual data from 1960 to 2008. The transmission elasticity from energy to the non-energy index is estimated at 0.28. At a more disaggregated level, the fertilizer index exhibited the largest elasticity (0.55), followed by precious metals (0.46), food (0.27), metals and minerals (0.25), and raw materials (0.11). By contrast, only a few price indices responded strongly to inflation, although the trend parameter estimate (often viewed as a proxy for technological progress) is negative for agriculture and positive for metals. A key implication of the pass-through results is that for as long as energy prices remain elevated, most non-energy commodity prices are expected to be high.